PENDEKATAN FILSAFAT HERMENEUTIKA DALAM PENAFSIRAN AL-QURAN: Transformasi Global Tafsir al-Quran - Mufid, Fathul (ULUL ALBAB Jurnal Studi Islam, 2011)
This essay will describe the transformation process of the interpretation of al Quran from the literal perspectives towards hermeneutics interpretations method, in a line with the recent globalization changes. Globalization is an era after modern where the world like a small village (global village), which makes interaction among countries, civilizations, religions, and cultures become more intens, fast and easy. This golbal changes is a medium which influencing cultures, countries, civilizations, and even religions aspects. Al Quran intepretation method which has been used by classical scholars stress more on the literal approach (tahlili) was considered to be irrelevant to answer and respon the current human problems in this globalization era. The advanced of the global information technology has brought positive impact for human life to fullfil their live needs. However, on the other side, golbalization brings negatives effect as well. For instance, since the information centers are controlled by advanced secular countries, the understanding of the Al Quran from various dimensions has shift and lose its function. These negatives effects are unavoidable for moslems which getting more influence on their religius life, including their understanding on the Holly Quran. Therefore, whether like or not, scholars in the intepretaion fields should adjust and inovate according to the current needs and trends using heurmenutics approach. Heurmenutics is a classical text critics method which is used to understand al Quran that contains God’s messages that should be understood, and used in our life practically and empirically.